Analisis Semiotika Charles Sanders Pierce terhadap Pencitraan Soeharto sebagai Bapak Pembangunan pada Era Orde Baru - Marya Ulfa Hidayah; Moch. Rikal Fahrizy; Wahibur Rohman; Moh. Dey Prayogo (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the representation of Soeharto as the “Father of Development” during the New Order era using Charles Sanders Peirce’s semiotic approach. This qualitative study applies semiotic analysis to three official photographs depicting Soeharto’s agricultural activities and infrastructure development inspections. The analysis employs Peirce’s triadic model, consisting of sign, object, and interpretant, along with the classification of signs into icons, indexes, and symbols. The findings reveal that the photographs constructed Soeharto’s leadership image through icons of direct involvement, indexes of government development achievements, and symbols of stability, prosperity, and political authority. The study concludes that visual representations during the New Order era functioned not merely as documentation but also as political communication instruments that constructed and legitimized power through systematic meaning production.